Pelatihan Dan Pendampingan Usaha Kreatif Pengolahan Keripik Kelapa Di Desa Gotakan Kulon Progo Yogyakarta - Mahfud Saepudin; Agus Juara; Nimatul Maula Azizah; Khofifah Indah Parawansa; Qurrota A’yun; Talita Humairoh; Sayyid Ahmad Haqqin Nazil; Diah Nilam Cahya; Nila Hilya Nafisa; Maulida Khofi Inayah; Taufik Taufik (Jurnal Pengabdian Masyarakat Madani, 2022)
The implementation of community service activities in the Gotakan Village of Kulon Progo is motivated by the community's livelihood in the agricultural and plantation sectors with plantation products in the form of coconut and bananas, but community income is still low due to lack of innovation in processing plantation products. Coconut is sold raw to collectors without being processed first, so the selling price is low. Therefore, it is necessary to provide assistance and training to the community in Gotakan Village to process plantation products. For this reason, this community service activity was provided with socialization and training on making coconut chips to the people of Gotakan Village. There are several programs that will be implemented related to the problems that have been described, namely providing socialization of the use of coconut fruit into coconut chips, providing training on coconut processing into innovative products and assistance for coconut chips business. The response of community leaders and residents to the realization of this training was very positive